2017
DOI: 10.1038/s41598-017-01351-w
|View full text |Cite
|
Sign up to set email alerts
|

Dual-cavity feedback assisted DFB narrow linewidth laser

Abstract: Single longitudinal mode (SLM) distributed feedback (DFB) lasers with a linewidth lower than a few kHz find applications in many coherent detection systems. In this paper, we proposed and experimentally demonstrated a novel method to compress the linewidth of a SLM DFB laser by utilizing a dual-cavity feedback structure (DCFS). The DCFS first provides optical self-injection feedback to compress the laser linewidth, and then the two feedback lengths are carefully optimized to achieve SLM output via the Vernier … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The regulating linewidth suggests that injection power is in the third regime of the feedback effects [6]. Considering strong injection power would lead to the mode-hopping in the main cavity [9], the measured injection power was limited to 1.4 μW. The SMSR of the DFB under the maximum injection power was confirmed to be 71 dB by DSHI (20 km delay fiber), as shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…The regulating linewidth suggests that injection power is in the third regime of the feedback effects [6]. Considering strong injection power would lead to the mode-hopping in the main cavity [9], the measured injection power was limited to 1.4 μW. The SMSR of the DFB under the maximum injection power was confirmed to be 71 dB by DSHI (20 km delay fiber), as shown in Fig.…”
Section: Resultsmentioning
confidence: 85%
“…1, happens to be the front mirror r2 of the LD. After this, the light signal I2 is divided into two signals, namely I3, which is the reflected, and I4, which becomes the transmitted light signal due to the reflection of FBG [36,37] arising from the impact of L  happens to be similar to that reported in [38]. However, the structures are different since our laser system consists of two FBGs and shorter fiber lengths.…”
Section: Principle and Simulationmentioning
confidence: 89%
“…Moreover, extensive research is today being performed on hardware and software solutions targeting power/cost reduction of coherent technology in the mid-to-long-term. Studies on self-coherent systems [28], [29], DSP-free configurations [23], low-power DSP [30], optical signal processing [23], [28], narrow-linewidth semiconductor low-cost lasers [31] and integration [32] are achieving ground-breaking results that will likely pave the way to the introduction of coherent in short reach communications. Some specific techno-economic studies tailored for 400G have shown that a single-wavelength coherent solution has very similar power consumption and ASIC footprint of a 4 lanes 100G DD solution [33].…”
Section: Discussionmentioning
confidence: 99%